Aplicación de la gestión del conocimiento en el “Fondo Nacional del Ahorro- FNA” (2023)
The purpose of this article is to analyze the changes and modifications in the profiles of individuals holding positions in the public entity such as the National Savings Fund, based on the application of holistic thinking and how it directly or indirectly affects changes in productivity that have been occurring over a period of 6 years up to the present. After interviewing some officials who had been hired within the specified timeframe, advantages and disadvantages are discovered in each of the training methods applied over these years. Additionally, improvements in the organization's productivity are observed, thanks to the implementation of new training techniques for officials.